Perspective: present pesticide discovery paradigms promote the evolution of resistance – learn from nature and prioritize multi‐target site inhibitor design - Gressel, Jonathan (Pest management science, 2020)
For many years, the emphasis of industry discovery programs has been on finding new target sites of pesticides and finding pesticides that inhibit single targets. There had been an emphasis on genomics in finding single targets for potential pesticides. There is also the claim that registration of single target inhibiting pesticides is simpler if the mode of action is known. Conversely, if one looks at the evolution of resistance from an epidemiological perspective to ascertain which pesticides have been the most recalcitrant to evolutionary forces, it is those that have multiple target sites of action. Non‐target‐site resistances can evolve to multi‐target‐site inhibitors, but these resistances can often be overcome by structural modification of the pesticide. Industry has looked at pest‐toxic natural products as pesticide leads, but seems to have abandoned those where they can find no single target of action. Perhaps nature has been intelligent and evolved many natural products that are synergistic multi‐target‐site inhibitors, and that is why natural compounds have been active for millennia? We should be learning from nature while combining new chemistry technologies with vast accrued databases and computer aided design allowing fragment‐based discovery and scaffold hopping to produce multi‐target site inhibitors instead of single target pesticides. © 2019 Society of Chemical Industry Pesticide discovery paradigm must be changed towards multi‐target‐site inhibitors to delay resistance.